Pengaruh Sales Growth, Likuiditas, dan Ukuran Perusahaan Terhadap Financial Distress - Ariyanti, Valentina; Dani Sopian (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
In this study, financial distress levels are measured using the Springate model method. Factors considered include sales growth, liquidity, and company size with the aim of investigating the impact of these three main factors on the potential for financial distress. The sample used comes from companies listed on the Bursa Efek Indonesia for a period of 5 years. The research method used a quantitative approach. The analysis results indicate that there is no multicollinearity with VIF values of 1.058 (Sales Growth), 1.004 (Liquidity), and 1.062 (Company Size) which are below 10. The residual distribution is normal with a sig value of 0.063, and there is no heteroskedasticity or autocorrelation with dU < d < 4-dU, meaning 1.6739 < 2.018 < 2.3261. Through hypothesis analysis, it was found that all variables studied actually have a simultaneous effect with significant values below 0.05, but only liquidity significantly influences the level of financial distress partially with a t-value of 6.256 > t-table 1.679.. Variable X is known to contribute 46% to the observed level of financial distress in the R square analysis. This finding indicates the need for further discussion to deeply understand the implications of this research.